Neuroprotective and antioxidant activities of saponins' mixture from Astragalus glycyphylloides in a model of 6-hydroxydopamine-induced oxidative stress on isolated rat brain synaptosomes - Magdalena Kondeva-Burdina; Ilina Krasteva; Georgi Popov; Vasil Manov (Pensoft Publishers, 2019)
The aim of the study was to investigate the possible neuroprotective and antioxidant activity of purified saponins'mixture (PSM), isolated from Astragalus glycyphylloides (Fabaceae), in a model of 6-hydroxydipamine (6-OHDA)-induced oxidative stress on isolated rat brain synaptosomes. Synaptosomes were incubated with 3 different concentrations of PSM: 60 µg/mL; 6 µg/mL; 0.6 µg/mL. The effects of PSM were compared to those of silymarin (S), at the same concentrations. The main parameters, characterized functional and metabolic status of synaptosomes, were investigated: viability (MTT-test) and level of reduced glutathione (GSH). At isolated rat brain synaptosomes, in conditions of 6-OHDA-induced oxidative stress (150 μМ), PSM revealed statistically significant, concentration-dependent, neuroprotective and antioxidant effects, compared to those of silymarin. Effects were most prominent at concentration 60 µg/mL. These neuroprotective effects of PSM might be due to the possible activity as scavenger of reactive oxygen species (ROS), produced by p-quinone (toxic metabolite of 6-OHDA).